2021
DOI: 10.1038/s41588-021-00812-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultraconserved enhancer function does not require perfect sequence conservation

Abstract: in ultraconserved enhancers result in very subtle but still selectively disadvantageous effects on gene expression, or additional, yet-to-be-identified, regulatory or nonregulatory functions of these sequences contribute to their extreme conservation in evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 39 publications
7
42
0
Order By: Relevance
“…In fact, a large fraction of H3K27ac-positive sequences detected either in the mouse or in the chicken PT cells were not conserved between the two species, suggesting that they evolved in a species-specific manner. In contrast, the high proportion of chicken promoters that display similar H3K27ac enrichments in mice, together with the similar expression patterns observed for mouse and chicken Hoxd genes in embryonic trunk cells, demonstrate that conserved gene expression can occur despite a high evolutionary plasticity in the cis -regulatory code usage, in agreement with previous reports (Berthelot et al, 2018; Snetkova et al, 2021). This may point to a regulatory strategy where multiple enhancers act coordinately to regulate the same target gene(s) thus creating a quantitive effect in a way similar to the reported action of super-enhancers (Sabari et al, 2018), yet where various subsets of CREs may display distinct tissue-specificities.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, a large fraction of H3K27ac-positive sequences detected either in the mouse or in the chicken PT cells were not conserved between the two species, suggesting that they evolved in a species-specific manner. In contrast, the high proportion of chicken promoters that display similar H3K27ac enrichments in mice, together with the similar expression patterns observed for mouse and chicken Hoxd genes in embryonic trunk cells, demonstrate that conserved gene expression can occur despite a high evolutionary plasticity in the cis -regulatory code usage, in agreement with previous reports (Berthelot et al, 2018; Snetkova et al, 2021). This may point to a regulatory strategy where multiple enhancers act coordinately to regulate the same target gene(s) thus creating a quantitive effect in a way similar to the reported action of super-enhancers (Sabari et al, 2018), yet where various subsets of CREs may display distinct tissue-specificities.…”
Section: Discussionsupporting
confidence: 92%
“…Based on phastCons scores, it indicates that these functionally conserved SEs do not necessarily exhibit higher scores than non-conserved ones. Consistently, a recent study suggests that the function of enhancer activities does not necessarily require the perfect sequence conservation (Snetkova et al, 2021). In fact, a previous study has also indicated that rarely conserved enhancers have overlapping functions even in phylogenetically distant species (Clarke et al, 2012;Villar et al, 2015).…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, our analyses show that only a small fraction of candidate CREs in Vitis leaf tissue are under sequence constraint, while the majority permit an average nucleotide diversity similar to random intergenic regions. These results are consistent with the rapid enhancer evolution recently documented in another plant species, cotton ( Gossypium hirsutum ; Wang et al., 2017 ), and multiple studies that suggest mutations drive beneficial variation and evolution in enhancers (Odom et al., 2007 ; Villar et al., 2015 ) and that, while enhancer function is conserved, enhancer sequence conservation is not required (Blow et al., 2010 ; Hare et al., 2008 ; Plessy et al., 2005 ; Snetkova et al., 2021 ). This apparent paradox in CRE maintenance likely reflects the coexistence of multiple enhancer types as previously described (Li et al., 2019 ), whose characteristics are obscured with ensemble analyses.…”
Section: Discussionmentioning
confidence: 97%